A longitudinal study of the correlation between coping style and post-traumatic growth in children and adolescents with a primary diagnosis of leukemia - Zhao, Shouju; Xiao, Xujia; Yang, Cheng; Xu, Min; Feng, Xianqiong (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the types of coping styles and changes in post-traumatic growth (PTG) among children and adolescents with leukemia at different treatment stages and to analyze the correlation between these factors.MethodsA convenience sampling method was used. A general information questionnaire, Revised Post-traumatic Growth Inventory for Children, and Coping with Disease scale were administered to 60 children diagnosed with leukemia before induction of remission (T1), after induction of remission but before consolidation therapy (T2), and after consolidation therapy but before maintenance therapy (T3).ResultsThe level of PTG in children with leukemia at the initial diagnosis was moderate, showed an upward trend, and then stabilized. Statistically significant differences were observed in the total PTG and new possibilities dimension scores at the three time points (P < 0.05). The most common coping style was “Acceptance,” followed by “Cognitive–Palliative,” while “Avoidance” was the least frequently used. The Acceptance dimension scores showed statistically significant differences at all three time points (P < 0.05). At all three time points, the Acceptance, Cognitive–Palliative, and Avoidance dimensions were positively correlated with the total PTG score (P < 0.05). At T2 and T3, the Avoidance dimension score was positively correlated with the total PTG score and all dimensions except Appreciation of Life (P < 0.05). At T3, the Emotional Reaction dimension was negatively correlated with total PTG score, relating to the Others and Personal Strength dimensions (P < 0.05).ConclusionThe growth levels of children and adolescents with newly diagnosed leukemia improved in the early stages of treatment following trauma; however, this improvement gradually leveled off as the disease progressed. A positive coping style can positively influence PTG, whereas a negative coping style is detrimental to psychological development. Therefore, healthcare providers should comprehensively, scientifically, and dynamically assess the coping styles and behavioral manifestations of patients during treatment, focusing on fostering a positive coping style that promotes psychological growth and enhances mental health.